Survival of resuscitated cardiac arrest patients with ST-elevation myocardial infarction (STEMI) conveyed directly to a Heart Attack Centre by ambulance clinicians. - Fothergill, Rachael T.; Watson, Lynne R.; Virdi, Gurkamal K.; Moore, Fionna P.; Whitbread, Mark (2013)
This study reports survival outcomes for patients resuscitated from out-of-hospital cardiac arrest (OHCA) subsequent to ST-elevation myocardial infarction (STEMI), and who were conveyed directly by ambulance clinicians to a specialist Heart Attack Centre for expert cardiology assessment, angiography and possible percutaneous coronary intervention (PCI).